Attenuation of β‐amyloid‐induced tauopathy via activation of CK2α/SIRT1: Targeting for cilostazol. Issue 2 (19th November 2013) - Lee, Hye Rin; Shin, Hwa Kyoung; Park, So Youn; Kim, Hye Young; Lee, Won Suk; Rhim, Byung Yong; Hong, Ki Whan; Kim, Chi Dae
Abstract : β‐Amyloid (Aβ) deposits and hyperphosphorylated tau aggregates are the chief hallmarks in the Alzheimer's disease (AD) brains, but the strategies for controlling these pathological events remain elusive. We hypothesized that CK2‐coupled SIRT1 activation stimulated by cilostazol suppresses tau acetylation (Ac‐tau) and tau phosphorylation (P‐tau) by inhibiting activation of P300 and GSK3β. Aβ was endogenously overproduced in N2a cells expressing human APP Swedish mutation (N2aSwe) by exposure to medium containing 1% fetal bovine serum for 24 hr. Increased Aβ accumulation was accompanied by increased Ac‐tau and P‐tau levels. Concomitantly, these cells showed increased P300 and GSK3β P‐Tyr216 expression; their expressions were significantly reduced by treatment with cilostazol (3–30 μM) and resveratrol (20 μM). Moreover, decreased expression of SIRT1 and its activity by Aβ were significantly reversed by cilostazol as by resveratrol. In addition, cilostazol strongly stimulated CK2α phosphorylation and its activity, and then stimulated SIRT1 phosphorylation. These effects were confirmed by using the pharmacological inhibitors KT5720 (1 μM, PKA inhibitor), TBCA (20 μM, inhibitor of CK2), and sirtinol (20 μM, SIRT1 inhibitor) as well as by SIRT1 gene silencing and overexpression techniques. In conclusion, increased cAMP‐dependent protein kinase‐linked CK2/SIRT1 expression by cilostazol can be a therapeutic strategy to suppress the tau‐related neurodegeneration in the AD brain. © 2013 Wiley Periodicals, Inc.